Combating plagiarism: the role of the health librarian. (December 2013) - Spring, Hannah; Adams, Rachel
Abstract This feature looks at the issue of plagiarism in health care students and the role of the health librarian in combating the problem. In particular, consideration is given to how plagiarism can occur and provides some examples from two UK universities of approaches health librarians can take in supporting students to avoid these common pitfalls. H.S.